2016
DOI: 10.1097/lgt.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management and Prognostic Factors of Vulvovaginal Melanoma

Abstract: Genital melanomas are characterized by a poor prognosis. Number of mitoses and lymph node status are the main factors influencing survival. Surgery is the mainstay of treatment. A correct and prompt diagnosis is paramount.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 18 publications
(28 reference statements)
2
34
0
Order By: Relevance
“…23). Further confounding the dilemma of staging and prognostication, PVMs have been historically characterized together with other melanomas arising on the female genitalia (notably, vaginal melanomas), further obscuring the prognostic features that might be specific to the vulvar origin (5,(24)(25)(26)(27)(28). Furthermore, most studies characterizing clinical and/or histopathologic parameters were often insufficiently powered to reveal relevant prognostic indicators, owing in large part to the relative rarity of PVM (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23). Further confounding the dilemma of staging and prognostication, PVMs have been historically characterized together with other melanomas arising on the female genitalia (notably, vaginal melanomas), further obscuring the prognostic features that might be specific to the vulvar origin (5,(24)(25)(26)(27)(28). Furthermore, most studies characterizing clinical and/or histopathologic parameters were often insufficiently powered to reveal relevant prognostic indicators, owing in large part to the relative rarity of PVM (29).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most studies characterizing clinical and/or histopathologic parameters were often insufficiently powered to reveal relevant prognostic indicators, owing in large part to the relative rarity of PVM (29). Nevertheless, many different clinical and histopathologic variables have been proffered to correlate with a higher risk of disease recurrence and survival in PVM, including higher age at diagnosis (4,(20)(21)(22)30), African American ethnicity (4,5,27,31), higher number of positive regional lymph nodes (4,22,24,29), central and/or multifocal vulvar involvement (21,22,26,30,32,33), increasing tumor thickness (3,9,20,21,(34)(35)(36)(37), ulceration (8,20,30,34,37), and dermal mitotic rate (8,20,24). Identification of the feature(s) among these that independently inform prognosis would greatly improve risk stratification and enable more personalized clinical management for patients with PVM, in particular, earlier and more aggressive intervention for those patients with highest risk disease.…”
Section: Introductionmentioning
confidence: 99%
“…2 Among those, 67 (68%) had VM. 3 In our study, we observed that nodal status is the main prognostic factor driving patients' prognosis, thus suggesting the importance of lymph node dissection in this cluster of patients. 2 Unfortunately, the study from Iacoponi et al 1 did not corroborate our results.…”
mentioning
confidence: 62%
“…3/14 vaginal melanomas had an NRAS mutation [7,20]. Median survival in patients who were black was significantly reduced; 16 months versus 39 months [9].…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors are debated (8), however a recent study showed mitotic count and lymph node status were the most important histological prognostic factors for disease free survival [9]. Mucosal melanosis, of which genital and specifically vaginal melanosis is a type, is a benign lesion which can mimic melanoma clinically [10][11][12].…”
Section: Discussionmentioning
confidence: 99%